Інформаційно-довідкове забезпечення органів державної влади - Швора, Оксана; Химиця, Наталія (Видавництво Львівської політехніки, 2013)
In the article the problem of information representative bodies to ensure feedback between citizens and the state, analyzed public relations as a mechanism of interaction between the state and civil society, , and generally describes the functionality of the web – sites of public authorities at regional level.
Keywords: інформація; органи державної влади; забезпечення; звернення громадян; довідкова інформація; зв’язки з громадськістю